The SU.FOL.OM3 Study: a secondary prevention trial testing the impact of supplementation with folate and B-vitamins and/or Omega-3 PUFA on fatal and non fatal cardiovascular events, design, methods and participants characteristics - Czernichow Sébastien; Blacher Jacque; Briancon Serge; Galan Pilar; Hercberg Serge (Trials, 2008)
Abstract Background During the last decades, many basic and clinical research have pointed to the role of B vitamins (folate, vitamins B6 and B12) and n-3 fatty acids as nutritional factors that might have a protective effect on the development of cardiovascular diseases (CVD). Methods/design The SU.FOL.OM3 (SUpplementation with FOlate, vitamin B6 and B12 and/or OMega-3 fatty acids) trial is a randomized double-blind, placebo-controlled, secondary-prevention trial designed to test the efficacy of 5-methyl tetra-hydro-folates (5-MTHF) supplementation, in combination with vitamin B6 and B12 and/or n-3 fatty acids, at nutritional doses, on fatal and non fatal ischemic CVD in a 2 × 2 factorial design. A total of 2501 patients aged between 45 and 80 years who had a past history, in the previous year, of myocardial infarction (n = 1151) or instable angina pectoris (n = 711) or an ischemic stroke (n = 639) were included. Subjects have to be supplemented and followed up for five years. Daily supplementation comprised nutritional doses of 5-MTHF (560 μg), vitamin B6 (3 mg) and B12 (20 μg) and/or n-3 fatty acids (600 mg with an EPA:DHA ratio of 2:1). A factorial design 2 × 2 has been applied to investigate the separate effects of the B-vitamins, and the n-3 fatty acids, as well as their interaction as compared to the placebo. The primary endpoint is a combination of myocardial infarction, ischemic stroke and cardiovascular death. Secondary endpoints are events of the composite endpoint taken separately, total mortality, and other cardiovascular events such as acute coronary syndromes, coronary revascularization, cardiac failure, arrhythmia... Conclusion Baseline socio-demographic and medical characteristics of participants are totally comparable in the four randomized groups. Trial registration Current Controlled Trials ISRCTN41926726